Registration of 3rd Dimension: the Context of Nepalese Cadastre - Bhatta, Ganesh Prasad; Khanal, Giri Raj; Sharma, Rabin Kaji (Journal on Geoinformatics, Nepal, 2005)
Registration of the ownership of a real estate property in Nepal is gaining its importance day by day. Before launching the Land Reform Program in 2021 by His Majesty’s Government of Nepal, the descriptive system of registration system was in use. After launching the Land Reform Program, the registration of real estate property was based on the map of the land unit occupied by it on the ground, i.e. registration of two dimensions. Gradually, the trend of owning a unit of space is increasing in recent days, needing the registration of the space, i.e. the third dimension. Joint Residential Buildings are examples such need. Although some juridical measures have already been formulated for the registration of 3rd dimension, the aspect of its’ visualization on a map, and some necessary measures are still lacking. The time has come to set necessary guidelines to tackle such shortcomings and face the challenges caused by the registration of third dimension. Based on this assumption, this paper highlights the existing scenarios, finds out the shortcomings and challenges in this regard, and suggests some necessary measures for solving the problems identified.